2010
DOI: 10.1007/s12272-010-0711-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological preconditioning by milrinone: Memory preserving and neuroprotective effect in ischemia-reperfusion injury in mice

Abstract: We tested the neuroprotective effect of milrinone, a phosphodiesterase III inhibitor, in pharmacological preconditioning. Bilateral carotid artery occlusion for 12 min followed by reperfusion for 24 h produced ischemia-reperfusion (I/R) cerebral injury in male Swiss albino mice. Cerebral infarct size was measured using triphenyltetrazolium chloride staining. Memory was assessed using the Morris water maze test, and motor coordination was evaluated using the inclined beam walking test, rota-rod test, and latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Similar results are also obtained in our previous work and also supported from other laboratories (Gulati et al, 2013;Sonkusare et al, 2005). All these mechanisms suggested that, I/R is known to cause impairment of cognitive function due to the damage of the cortex and hippocampal neurons (Morganti and Riva, 2014;Vallejo et al, 2014) along with impairment of motor disability (Biala et al, 2013;Gulati et al, 2013;Saklani et al, 2010). The administration of calcium channel antagonist is ameliorating I/R induced cognitive and motor dysfunctions (Gulati et al, 2013;Kaur et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results are also obtained in our previous work and also supported from other laboratories (Gulati et al, 2013;Sonkusare et al, 2005). All these mechanisms suggested that, I/R is known to cause impairment of cognitive function due to the damage of the cortex and hippocampal neurons (Morganti and Riva, 2014;Vallejo et al, 2014) along with impairment of motor disability (Biala et al, 2013;Gulati et al, 2013;Saklani et al, 2010). The administration of calcium channel antagonist is ameliorating I/R induced cognitive and motor dysfunctions (Gulati et al, 2013;Kaur et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…The grip strength was assessed by using a lateral push method as an index of resistance response against lateral push stimuli from either side of the shoulder as described by method of Saklani et al (2010) with slight modification of Gulati et al (2013). Briefly, mice were placed on clean tile surface and applied lateral push stimuli (by applying gentile force with transparent measuring scale) 5 times on each side of the shoulder.…”
Section: Assessment Of Grip Strength By Lateral Push Testmentioning
confidence: 99%
“…For example, olprinone and milrinone provided significant neuroprotection after cerebral ischemia/reperfusion injury in rats (Saklani et al, 2010; Genovese et al, 2011). Zaprinast and other PDE5 inhibitors improved memory (Prickaerts et al, 2004), and propentofylline improved learning and memory deficits induced by beta-amyloid protein (Yamada et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In animals, different neuroprotective treatments have exhibited varying results depending upon which cognitive aspects were tested. For example, IPC [227], pharmacological preconditioning [228, 229], or ischemic postconditioning [230] have displayed improvements in spatial memory after global cerebral ischemia. Caloric restriction [171] and isoflurane preconditioning [231] before global cerebral ischemia displayed improvements in working memory.…”
Section: Global Cerebral Ischemia and Cognitive Dysfunctionmentioning
confidence: 99%